Leveraging change in ecosystem restoration: from planting trees to regenerating people-nature systems - Frietsch, Marina; Kaplin, Beth A.; Mukuralinda, Athanase; Nkurikiyimana, Donath; William, Appollinaire; Bariyanga, Jean Damascene; Duguma, Dula Wakassa; Kayitanirwa, Cecile; Mujawamariya, Myriam; Nsengimana, Venuste; Nshimyumuremyi, Pierre; Nyiramvuyekure, Verene; et al. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Despite calls for more integrated ecosystem restoration approaches, many restoration projects continue to focus on simple metrics capturing isolated ecological or social system dimensions. To realize the potential of ecosystem restoration to generate a multitude of desirable social-ecological outcomes, we argue that a change in mindsets is needed to move from planting trees to regenerating people-nature systems. Drawing on a leverage points perspective, we propose that changing the paradigms that underpin restoration could shift the modus operandi from an instrumental perspective of ‘nature for people’ to a relational perspective of ‘people with nature’. Following three interacting realms of leverage for transformational change, we use the case study of western Rwanda to exemplarily illustrate how restoration can serve as a critical entry point for re-connecting people and nature in degraded landscapes, re-structuring the time scales considered in natural resource management, and re-thinking the use of diverse types of knowledge in this context. Combining these three realms in place-based restoration efforts can inform new avenues for ecosystem restoration that are rooted in genuine social-ecological relationships. This, in turn, could trigger regenerative dynamics in restoration landscapes – i.e., mutually reinforcing dynamics that support both human and non-human wellbeing. This approach reflects a broader transition from repairing fragmented landscape elements to regenerating integrated social–ecological systems.
Keywords: Ecosystem Restoration; Forest Landscape Restoration; Leverage Point; Social-ecological System; Regeneration